Aspectos do bilinguismo alemão-português na comunidades de Mondaí e São João do Oeste - SC - Wolschick, Isaura (2016)
The aim of this study is to describe aspects of the German-Portuguese bilingualism in the communities of Mondaí and São João do Oeste - SC. German descendants, originaly from Rio Grande do Sul, and German speaking immigrants from Europe colonized both towns. The colonization of Mondaí began in 1922 and that of São João in 1926. Despite all these years, the Vargas government's nationalization policy and linguistic discrimination suffered by minority languages, the German language persists in these two communities. In order to describe bilingualism in the communities mentioned above, we used the methodology guided by the multidimensional dialectology. With that in mind, eight informants were interviewed, eight informants in each community, which gives a total of sixteen informants. Of the eight chosen informants, four are men and four are women. Two of them belong to the GI (generation one – 18-36 years), one belonging to the Ca (upper class) and the other one to the Cb (lower class). The other two women and men belong to the GII (Generation Two - over 55 years), one belonging to the Ca and the other one to the Cb. The requirements for choosing the informants were two: the informants must have lived 3/4 of their lives in these communities and they must have German as their mother tongue. In addition to the questionnaire, we also asked the respondents to read and to write a short essay in German, and to translate some words from Portuguese into German. Our goal with these instruments was to investigate the informants’ oral, listening, writing and reading skills, and to ascertain for what functions, when, with whom and where the informants use their two languages. The analysis of the survey data showed that 100% of the informants from both towns see themselves as bilinguals and that 37.5% of the respondents, from Mondai and São João, are simultaneous bilinguals and 62.50% of the informants, from both towns, are consecutive bilinguals, meaning they have learnt first German and then Portuguese. Regarding the functions to what the informants use their languages, it was found that the community of São João do Oeste has more contact areas than Mondaí, where the dominant language is Portuguese. It was also possible to verify that women are more inclined to language substitution in favor of the majority language, which seems to be true for the upper class. With respect to the degree of bilingualism, it was found that the German variety is, basically, an oral language, that is, few informants can read and write in this language.